The Model of Associations Between Self-Assessed Critical Thinking Skills, Their Perceived Importance and Work Engagement - Aistė Diržytė; Justinas Sadauskas; Valdonė Indrašienė; Violeta Jegelevičienė; Odeta Merfeldaitė; Daiva Penkauskienė; Jolanta Pivorienė; Asta Railienė (Social Welfare: Interdisciplinary Approach)
he purpose of this study was to explore the links between the perceived importance of critical thinking skills, self-reported critical thinking skills, and work engagement. The study applied a cross-sectional design, and the sample consisted of 2012 employees; the mean age was 41.93 (SD=11.42). To analyse the links between the constructs, three instruments were used: The Work Engagement Scale (UWES), The Perceived Importance of the Critical Thinking Skills Scale (PICTS), and The self-reported Critical Thinking Skills Scale (CTS). For the statistical analyses, SPSS v.26.0, AMOS v.26.0, JASP v.18, and JAMOVI v.2.2.1 software was applied. Confirmatory factor analyses showed the acceptable model fit and validity of the scales in the Lithuanian population.